Fertilization strategies and liming in no-till integrated crop–livestock systems: effects on phosphorus and potassium use efficiency - Lucas Aquino Alves; Luiz Gustavo de Oliveira Denardin; Gustavo Duarte Farias; João Pedro Moro Flores; Dionata Filippi; Carolina Bremm; Paulo César de Faccio Carvalho; Amanda Posselt Martins; Luciano Colpo Gatiboni; Tales Tiecher (Revista Brasileira de Ciência do Solo, 2022)
ABSTRACT In an integrated crop-livestock system (ICLS), system fertilization exploits the nutrient cycling imposed by animal grazing and increases the system efficiency. An increasingly popular approach to fertilization in southern Brazil is anticipating P and K requirements for soybeans into the pasture phase. This can increase the use efficiency of these nutrients in ICLS based on meat production in winter and soybean in summer. This study aimed to evaluate the effect of fertilization strategy, grazing and soil acidity correction on herbage and animal production, soybean yield, P and K contents in soil and plant tissue, and P and K use and economic efficiency. In 2017, a field experiment was established on an Acrisol ( Argissolo Vermelho distrófico ) double-cropped with soybean and Italian ryegrass under no-tillage. Herbage and animal production, soybean yield, available P and K contents, and P and K plant tissue status were determined. Available P and K in the soil were unaffected by grazing and fertilization strategy. Conversely, system fertilization and liming increased the P and K contents of aboveground Italian ryegrass biomass. Additionally, the available K budget in the soil was 2.7 times smaller in the integrated system with system fertilization than in the specialized system with conventional fertilization, possibly due to K fixation in non-exchangeable forms. By contrast, the available P budget in the soil was not affected by treatments and was positive with all systems. The use of ICLS increased economic return, and P and K use efficiency for protein production. System fertilization did not affect soybean yield, but it increased the total herbage production of Italian ryegrass. Despite this, sheep live weight did not increase. Using ICLS in combination with system fertilization provides an effective nutrient management strategy with a higher potential for sustainable food production when compared with conventional fertilization.